Synthesis and Characterization of Poly (β-amino Ester) and Applied PEGylated and Non-PEGylated Poly (β-amino ester)/Plasmid DNA Nanoparticles for Efficient Gene Delivery - Iqbal, Sajid; Martins, Alessandro F.; Sohail, Muhammad; Zhao, Jingjing; Deng, Qi; Li, Muhan; Zhao, Zhongxi (Frontiers in Pharmacology, 2022)
Polymer-based nanocarriers requires extensive knowledge of their chemistries to learn functionalization strategies and understand the nature of interactions that they establish with biological entities. In this research, the poly (β-amino ester) (PβAE-447) was synthesized and characterized, aimed to identify the influence of some key parameters in the formulation process. Initially; PβAE-447 was characterized for aqueous solubility, swelling capacity, proton buffering ability, and cytotoxicity study before nanoparticles formulation. Interestingly, the polymer-supported higher cell viability than the Polyethylenimine (PEI) at 100 μg/mL. PβAE-447 complexed with plasmid DNA (pDNA) generated nanocarriers of 184 nm hydrodynamic radius (+7.42 mV Zeta potential) for cell transfection. Transfection assays performed with PEGylated and lyophilized PβAE-447/pDNA complexes on HEK-293, BEAS-2B, and A549 cell lines showed better transfection than PEI. The outcomes toward A549 cells (above 66%) showed the highest transfection efficiency compared to the other cell lines. Altogether, these results suggested that characterizing physicochemical properties pave the way to design a new generation of PβAE-447 for gene delivery.